Phytochemical investigation and diuretic activity of Cyclea peltata leaf extracts - K K Hullatti; U V Gopikrishna; I J Kuppast (Wolters Kluwer Medknow Publications, 2011)
Ayurvedic system of medicine is well known for treating renal problems. A vast number of medicinal plants mentioned in Ayurvedic system of medicine are known to possess diuretic properties. Present study reports the preliminary phytochemical investigation of petroleum ether and ethanolic extracts of Cyclea peltata and their diuretic activity. Preliminary phytochemical screening reveals the presence of phytosterols and alkaloids as major phytoconstituents in petroleum ether extract. The ethanolic extract showed the presence of alkaloids, flavonoids, tannins, diterpenes and saponins. Pharmacological investigation revealed that ethanolic extract of C. peltata leaves possessed significant diuretic activity in a given dose of 200 and 300 mg/kg body weight (Diuretic action 1.7 and 2.6, respectively). Where as petroleum ether extract has shown moderate diuresis at a dose of 300 mg/kg body weight (Diuretic action 1.1). The present study justifies the use of C. peltata in the Ayurvedic system of medicine as a diuretic drug.